2007
DOI: 10.1128/jvi.02357-06
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Human Immunodeficiency Virus Type 1 Postentry Infection Processes: Evidence against Disproportionate Numbers of Defective Virions

Abstract: The vast majority of human immunodeficiency virus type 1 particles are claimed to be noninfectious, but there is disagreement as to whether they are defective or simply lack the opportunity to initiate an infection. We have examined the efficiencies of reverse transcription and integration and find that approximately 1 of every 8 virions that initiate reverse transcription form proviruses, a quantity significantly different from the commonly reported ratio of 1 in 1,000. In addition, results from two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
83
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 46 publications
(50 reference statements)
4
83
1
Order By: Relevance
“…This result was unexpected, given the previous rough estimates of the genome RNA content of virions and the high efficiency of virion formation that occurs in the absence of genome RNA. A recent study indicated that, under optimal conditions, 1 in 8 to 1 in 20 virions can initiate an infection event, despite earlier estimates that a large portion of HIV-1 particles is noninfectious (22). Our results indicate that most of viral particles have full-length viral RNAs and a low efficiency of genomic RNA packaging is not a major contributor to the formation of noninfectious virions.…”
Section: Discussioncontrasting
confidence: 48%
“…This result was unexpected, given the previous rough estimates of the genome RNA content of virions and the high efficiency of virion formation that occurs in the absence of genome RNA. A recent study indicated that, under optimal conditions, 1 in 8 to 1 in 20 virions can initiate an infection event, despite earlier estimates that a large portion of HIV-1 particles is noninfectious (22). Our results indicate that most of viral particles have full-length viral RNAs and a low efficiency of genomic RNA packaging is not a major contributor to the formation of noninfectious virions.…”
Section: Discussioncontrasting
confidence: 48%
“…However, the vast majority of these infecting viral particles have been reported to be noninfectious (22,30). Emerging evidence suggests that this may actually be an overestimation of defective virions and that Ïł1 in 10 viral particles is infectious (39). Even if we assume this higher estimate (1:10), then according to our dose-response analysis, infection with 2 to 10 infectious virions/cell is sufficient for presentation of incoming virion proteins.…”
Section: Discussionmentioning
confidence: 63%
“…It has been estimated that more than 90% of the complete linear viral DNAs made in cultured cells are successfully integrated (31,32). However, the fact that both of the CBD-IBD fusions we tested strongly enhanced titer in MEF-KO cells shows that both support efficient integration and high-level expression of the resulting proviruses.…”
Section: Discussionmentioning
confidence: 76%